Factors Relating to the Activity of Mother’s Visits to the Posyandu - Yeti Trisnawati; Nining Sulistyowati; Etika Khoiriyah; Ani Mulyandari; Putri Yuriati (International Journal of Public Health Excellence (IJPHE), 2024)
A significant indicator that contributes to lessening efforts is the number of toddler trips to Posyandu. In the operational area of Tanjungpinang City's Mekarbaru Health Center, 36.40% of visitors are Posyandu visits in 2023. This coverage continues to fall well short of both national and provincial statistics, as well as the government's accomplishment goals. The purpose of this study is to determine the characteristics that influence toddler visits to Posyandu, Batu IX Village, Mekar Baru Health Center Working Area, Tanjungpinang City, in the province of the Riau Islands. With a cross-sectional methodology and a purposive sample strategy, 191 mothers of toddlers between the ages of 13 and 59 months make up the sample size for this kind of quantitative study. Surveys were used to collect measurements. The statistical test of chi-square was applied in data analysis. The findings of the study indicate that moms of toddlers who visit Posyandu have a relationship with perceptions of Posyandu services (p=0.001; OR=2.735) and family support (p = 0.000; OR=3.237). The mother's age, education, occupation, knowledge, and attitude have little bearing on how frequently she visits Posyandu. It was determined that the frequency of posyandu visits by mothers of toddlers at the Posyandu in the Mekar Baru Community Health Center Working Area was highly correlated with family support and perceptions of posyandu services.